Beyond landscape's visible realm: Recorded sound, nature, and wellbeing. (January 2020) - Bates, Victoria; Hickman, Clare; Manchester, Helen; Prior, Jonathan; Singer, Stephanie
Abstract: This article draws on an AHRC/EPSRC funded project called 'A Sense of Place: Exploring nature and wellbeing through the non-visual senses'. The project used sound and smell technologies, as well as material textures and touch, to ask: what does 'wellbeing' mean for people in relation to the non-visual aspects of nature, and how might technology play a role in promoting it (if at all)? This article takes recorded sound as a case study. It argues that recorded soundscapes should be understood on their own terms rather than as 'less than' or a simulation of natural environments. They have specific value in creating space for imagination, particularly when delivered with care and as part of the co-creation of sensory experience. Overall, the article argues that the value of emerging immersive technologies is not to simulate nature better. An 'immersive experience' is richest when it allows for – and reveals – the nuances and complexities of individual responses to natural environments. Highlights: A case study of nature and recorded sound indicates that there is no simple relationship between 'nature' and 'wellbeing'. Individual responses to natural environments are personal and complex, shaped by life history and experiences. Recorded sound is a specific kind of auditory encounter, not just a diluted or diminished version of 'real' experiences of nature. The value of recorded soundscapes lies not in their ability to simulate nature, but in their capacity to stimulate imagination. Personal care is a crucial part of the delivery of sensory technologies and allows for the co-creation of sensory experiences.